Comparative study of the glucose and trehalose addition on the extenders for goat sperm liquid storage. - Alam, Md Emtiaj; Yeasmin, Most Shorifa; Das, Dipak Kumar; Islam, Md Shohidul; Ahmed, Soshe; Islam, Md Hamidul; Islam, Md Akhtarul; Kamal, Md Mostofa; Kabir, Aurangazeb; Khan, Alam; Haque, Md Hakimul; Masum, Md Abdul; et al. (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: The objective of this study was to assess the effects of varying glucose and trehalose concentrations on tris-citric acid-egg yolk-fructose (TCEF) diluents for the short-term cold storage of goat semen. Materials and Methods: The semen sample was collected, unwashed, and divided into the following groups: control (TCEF without glucose and trehalose), TCEF + glucose (75, 150 mm), and TCEF + trehalose (75, 150 mm). Each experimental sperm group (sperm concentration: 9 × ×107 / ml) was kept at 4°C in a refrigerator. The impact of varying glucose and trehalose levels on the quality of the spermatozoa was assessed at different time points: after dilution and at 5, 24, 48, and 72 h of refrigeration. Results: After dilution, progressive motility (PM), total motility (TM), sperm viability (SV), functional integrity (FI), and acrosome integrity of G-75, G-150, T-75, and T-150 did not differ significantly from the control. The PM, TM, SV, FI, and acrosome integrity of sperm of T-150 were considerably lower than the control, G-75, G-150, and T-75 after 5 and 24 h of cool storage. The T-75 group showed superior PM, TM, and FI after 48 h of cool storage, with noticeably greater values than the other groups. Conclusion: This study indicates that trehalose is a more favorable sugar than glucose for 48 h cool storage of buck semen, providing greater advantages in PM, TM, and PMI. J. Adv. Vet. Anim. Res., 12(1): 287–296, March 2025 http://doi.org/10.5455/javar.2025.l895